Risk Factors and Predictors of Subsequent ACL Injury in Either Knee After ACL Reconstruction: Prospective Analysis of 2488 Primary ACL Reconstructions From the MOON Cohort. (July 2015) - Kaeding, Christopher C.; Pedroza, Angela D.; Reinke, Emily K.; Huston, Laura J.; ,; Spindler, Kurt P.
Background: Anterior cruciate ligament (ACL) reinjury results in worse outcomes and increases the risk of posttraumatic osteoarthritis. Purpose: To identify the risk factors for both ipsilateral and contralateral ACL tears after primary ACL reconstruction (ACLR). Study Design: Cohort study; Level of evidence, 3. Methods: Data from the Multicenter Orthopaedic Outcomes Network (MOON), a prospective longitudinal cohort, were used to identify risk factors for ACL retear. Subjects with primary ACLR, no history of contralateral knee surgery, and a minimum of 2-year follow-up data were included. Age, sex, Marx activity score, graft type, lateral meniscal tear, medial meniscal tear, sport played at index injury, and surgical facility were evaluated to determine their contribution to both ipsilateral retear and contralateral ACL tear. Results: A total of 2683 subjects with average age of 27 ± 11 years (1498 men; 56%) met all study inclusion/exclusion criteria. Overall there were 4.4% ipsilateral graft tears and 3.5% contralateral ACL tears. The odds of ipsilateral ACL retear were 5.2 times greater for an allograft ( P < .01) compared with a bone–patellar tendon–bone (BTB) autograft; the odds of retear were not significantly different between BTB autograft and hamstring autograft ( P = .12). The odds of an ipsilateral ACL retear decreased by 0.09 for every yearly increase in age ( P < .01) and increased by 0.11 for every increased point on the Marx score ( P < .01). These odds were not significantly influenced by sex, smoking status, sport played, medial or lateral meniscal tear, or consortium site ( P > .05). The odds of a contralateral ACL tear decreased by 0.04 for every yearly increase in age ( P = .04) and increased by 0.12 for every increased point on the Marx score ( P < .01); these odds were not significantly different between sex, smoking status, sport played, graft type, medial meniscal tear, or lateral meniscal tear ( P > .05). Conclusion: Younger age, higher activity level, and allograft graft type were predictors of increased odds of ipsilateral graft failure. Higher activity and younger age were found to be risk factors in contralateral ACL tears.